'She Was Such an Exotic Creature': Feeding the Orientalist Machine in Agatha Christie's Murder in Mesopotamia. (September 2021) - Pujolràs-Noguer, Esther
Abstract : The Orientalist scenario that Agatha Christie's Murder in Mesopotamia displays is an incontestable representation of the 'Orient' as an exoticised 'Other' that menaces Western civilization with its inherent tendency towards depravation and savagery. In Christie's novel, the archaeological site configures a terrain wherein civilisation is safeguarded because controlled by Westerners and yet, civilisation is disrupted the moment a murder is committed and everything indicates that the murderer is 'one of us', not the oriental 'Other'. However, the stranger that endangers the civilising integrity of an otherwise unpolluted, commendable Orientalist enterprise by murdering 'one of us' is none other than the victim, Mrs Leidner, who goes through an orientalising process that premeditatedly transforms her into the essential Oriental female, the Belle Dame sans Merci. This article aims at unmasking how the Orientalist plot of Murder in Mesopotamia is strategically used to condemn the woman, the victim, and exonerate the murderer, the husband. Hence, the 'Oriental' female that lurks behind Mrs Leidner's 'blonde, Scandinavian fairness' ( Mesopotamia 28) is exposed whereas Dr Leidner's past as a German spy is conspicuously undermined. What this Orientalist plot ultimately unveils is the prescience of 'whiteness' as a discursively constructed category just as elusive as gender.